Methodological Tools for the Detection of Risks to the Welfare of the Individuals and the Territory of Residence - Kuklin, Aleksandr Anatolyevich; Pecherkina, Maria Sergeevna; Tyrsin, Aleksandr Nikolaevich; Surina, Alfiya Adgamivna (Economy of Regions, 2017)
To formalise the assessment of risks to the welfare of individuals and the territory of residence presents a relevant issue. This study aims to define the economic security in the structure of the system of the welfare of individuals and the territory of residence and to develop a classifier of risks. We consider the economic security as one of the needs for meeting which the welfare aims. The risk assessment includes three stages. At the first stage, we calculate the welfare of individuals and the territory. At the second stage, the authors determine the coefficient of variation to select indicators that will characterize the risks to the welfare. The third stage assumes the assessment of these risks, which reduce the welfare. The regional economic system is considered as a multidimensional stochastic system, which can be modelled as a vector random variable. The components of this variable generally are mutually correlated. The formalization of the assessment of risks to the welfare is based on this interpretation of the regional economic system. As a result, the authors highlighted the main threats to the welfare of individuals and the territory of residence. We have selected risk factors with high coefficient of variation, which indicates that the selected indicators have a high degree of variability. The research evaluates risks to the welfare of individuals and the territory of residence assessing the probability of the occurrence of crisis states for the regions of the Ural Federal District. The probabilities of the states pre-crisis 1 and pre-crisis 2 for all these regions are sufficiently high. It can indicate that the general social and economic state in the regions of the Ural Federal District is unstable. The findings can be used to develop an effective risk management system at the regional level.